Dalit and Tribal Christians of India ;- Issues ande Challenges - Thomas, V.V. (Kerala Focus India Trust, 2014)
Its a book that deals with the history of christianity among the Dalits and the tribal people of India
Keywords: India-Tribal Community -- India-Dalit -- History of Christianity amoung Dalit or Tribes in India